2018
DOI: 10.3389/fmicb.2018.00693
|View full text |Cite
|
Sign up to set email alerts
|

A Carbohydrate Moiety of Secreted Stage-Specific Glycoprotein 4 Participates in Host Cell Invasion by Trypanosoma cruzi Extracellular Amastigotes

Abstract: Trypanosoma cruzi is the etiologic agent of Chagas’ disease. It is known that amastigotes derived from trypomastigotes in the extracellular milieu are infective in vitro and in vivo. Extracellular amastigotes (EAs) have a stage-specific surface antigen called Ssp-4, a GPI-anchored glycoprotein that is secreted by the parasites. By immunoprecipitation with the Ssp-4-specific monoclonal antibodies (mAb) 2C2 and 1D9, we isolated the glycoprotein from EAs. By mass spectrometry, we identified the core protein of Ss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 52 publications
(67 reference statements)
0
20
0
1
Order By: Relevance
“…The extracellular amastigotes share morphological, immunological and infective properties with the intracellular counterparts. β-Galactopyranosides were identified as determinants in Ssp4 of host–cell interactions [ 59 ], but the linkage to the protein and the structure of the oligosaccharides were not defined.…”
Section: The Glycan In Mucins Of T Cruzimentioning
confidence: 99%
See 1 more Smart Citation
“…The extracellular amastigotes share morphological, immunological and infective properties with the intracellular counterparts. β-Galactopyranosides were identified as determinants in Ssp4 of host–cell interactions [ 59 ], but the linkage to the protein and the structure of the oligosaccharides were not defined.…”
Section: The Glycan In Mucins Of T Cruzimentioning
confidence: 99%
“…They found that the galectins bind preferentially to amastigotes. Although amastigotes lack mucins, β-galactopyranosides have been identified as determinants for host–cell interactions in the specific glycoprotein Ssp4 [ 59 ]. The fine glycan structure of Ssp4 was not reported.…”
Section: Potential Role Of Galectins In the Infection Of mentioning
confidence: 99%
“…(8) Various molecules participate in the inflammatory condition in Chagas disease, among which, galactic 3 (Gal-3). (9,10) It has been demonstrated that T. cruzi uses Gal-3 to interact with laminin, the primary constituent of basal membranes, promoting fixation and entrance of the parasite. (11) On the other hand, the lower expression of Gal-3 favors the multiplication of amastigotes, which suggests that this galectin develops control throughout the chagasic infection.…”
Section: ❚ Resumomentioning
confidence: 99%
“… Extracellular amastigotes (EAs) of T. cruzi release microvesicles over cellular or non-cellular surfaces. (A) EAs can release microvesicles trails (arrowhead) over acellular surfaces such as uncoated transwell membrane (scanning electron microscopy) ( Florentino et al, 2018 ). (B) EAs can also secrete microvesicle trails over HeLa cells ( Florentino et al, 2018 ).…”
Section: Cups As Synaptic Junctions and Phagocytosismentioning
confidence: 99%
“…(A) EAs can release microvesicles trails (arrowhead) over acellular surfaces such as uncoated transwell membrane (scanning electron microscopy) ( Florentino et al, 2018 ). (B) EAs can also secrete microvesicle trails over HeLa cells ( Florentino et al, 2018 ). In this particular interaction, microvesicle trails (arrowheads) were secreted inside the actin-rich cup-like structure induced on the surface of HeLa cells by the EA (3D rendering of confocal microscopy acquisition).…”
Section: Cups As Synaptic Junctions and Phagocytosismentioning
confidence: 99%